Experimental and computational analysis of biased agonism on full-length and a C-terminally truncated adenosine A2A receptor - Gemma Navarro; Angel Gonzalez; Stefano Campanacci; Rafael Rivas-Santisteban; Irene Reyes-Resina; Nil Casajuana-Martin; Arnau Cordomí; Leonardo Pardo; Rafael Franco (Computational and Structural Biotechnology Journal, 2020)
Biased agonism, the ability of agonists to differentially activate downstream signaling pathways by stabilizing specific receptor conformations, is a key issue for G protein-coupled receptor (GPCR) signaling. The C-terminal domain might influence this functional selectivity of GPCRs as it engages G proteins, GPCR kinases, β-arrestins, and several other proteins. Thus, the aim of this paper is to compare the agonist-dependent selectivity for intracellular pathways in a heterologous system expressing the full-length (A2AR) and a C-tail truncated (A2AΔ40R lacking the last 40 amino acids) adenosine A2A receptor, a GPCR that is already targeted in Parkinson’s disease using a first-in-class drug. Experimental data such as ligand binding, cAMP production, β-arrestin recruitment, ERK1/2 phosphorylation and dynamic mass redistribution assays, which correspond to different aspects of signal transduction, were measured upon the action of structurally diverse compounds (the agonists adenosine, NECA, CGS-21680, PSB-0777 and LUF-5834 and the SCH-58261 antagonist) in cells expressing A2AR and A2AΔ40R. The results show that taking cAMP levels and the endogenous adenosine agonist as references, the main difference in bias was obtained with PSB-0777 and LUF-5834. The C-terminus is dispensable for both G-protein and β-arrestin recruitment and also for MAPK activation. Unrestrained molecular dynamics simulations, at the μs timescale, were used to understand the structural arrangements of the binding cavity, triggered by these chemically different agonists, facilitating G protein binding with different efficacy.